The Effect of Real-Time Feedback Using a Smartwatch on the Clinical Behavior of Novice Student Clinicians. - Scott, Courtney G.; Becker, Trina M.; Simpson, Kenneth O. (Perspectives of the ASHA Special Interest Groups, 2017)
The use of computer monitors to provide technology-based written feedback during clinical sessions, referred to as "bug-in-the-eye" (BITi) feedback, recently emerged in the literature with preliminary evidence to support its effectiveness (Carmel, Villatte, Rosenthal, Chalker & Comtois, 2015; Weck et al., 2016). This investigation employed a single-subject, sequential A-B design with two participants to observe the effects of implementing BITi feedback using a smartwatch on the clinical behavior of student clinicians (SCs). Baseline and treatment data on the stimulus-response-consequence (S-R-C) contingency completion rates of SCs were collected using 10 minute segments of recorded therapy sessions. All participants were students enrolled in a clinical practicum experience in a communication disorders and sciences (CDS) program. A celeration line, descriptive statistics, and stability band were used to analyze the data by slope, trend, and variability. Results demonstrated a significant correlative relationship between BITi feedback with a smartwatch and an increase in positive clinical behaviors. Based on qualitative interviews and exit rating scales, SCs reported BITi feedback was noninvasive and minimally distracting. Preliminary evidence suggests BITi feedback with a smartwatch may be an effective tool for providing real-time clinical feedback.